Autonomous Units for Solving the Capacitated Vehicle Routing Problem Based on Ant Colony Optimization - Kuske, Sabine; Luderer, Melanie (Electronic Communications of the EASST, 2010)
Communities of autonomous units and ant colony systems have fundamental features in common. Both consists of a set of autonomously acting units that transform and move around a common environment that is usually a graph. In contrast to ant colony systems, the actions of autonomous units are specified by graph transformation rules which have a precisely defined operational semantics and can be visualized in a straightforward way. In this paper, we model an ant colony system solving the capacitated vehicle routing problem as a community of autonomous units. The presented case study shows that the main characteristics of ant colony systems such as tour construction and pheromone updates can be captured in a natural way by autonomous units.